Ocular myiasis in a glioma: a case report - Mathew, David J.; Selvin, Satheesh Solomon T.; Kuruvilla, Shilpa E.; Kuriakose, Thomas (Nepalese Journal of Ophthalmology, 2017)
Background: Ocular myiasis though rare, is usually found in association with basal cell carcinoma. It is rarer still in tumors other than basal cell carcinoma. We report a case of ocular myiasis in a glioma which is hitherto unreported to the best of our knowledge. Case: A 50 year old male presented with bleeding and maggots emanating from a tumourous outgrowth which had replaced his right eye. He complained of swelling and pain in his right eye for the last 2 years. Manual removal of maggots was carried out following which he underwent total excision of the mass and local debridement. Biopsy of the mass was consistent with astrocytoma. Conclusion: Myiasis though rare should be suspected in long standing neglected lesions with suggestive history. Infection, ischemic necrosis and malignancy coupled with overcrowding, poor living conditions, presence of excessive arthropods in the locality and low levels of hygiene drastically increase the risk of myiasis.